(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2023)
Objective: To investigate the knowledge of nursing students about intestinal elimination stomas. Method: Descriptive, exploratory, analytical study, with a quantitative approach, carried out in a public higher education institution in Piauí, Brazil, with 115 nursing students between the eighth and the tenth period of the course. The data collection was carried out through an online questionnaire composed of two instruments, one about the sociodemographic and school profile of the students, and the other about knowledge on intestinal ostomies or elimination. Data analysis was carried out through descriptive analysis (absolute and relative frequencies, means and standard deviation) and inferential analysis, in order to verify association between variables, with χ2 and Fisher’s exact tests. Results: Most nursing students have a deficit regarding aspects related to preoperative and immediate and mediate postoperative care. There was a statistically significant difference in the academic performance index variable, and it was observed that students with academic performance greater than 9 obtained a higher number of correct answers compared to the others. Conclusion: There are knowledge gapsamong nursing students, especially in nursing care in preoperative care, and in the immediate and mediate postoperative period, which in turn can compromise the quality of care provided.